TRANSFER FACTOR OF SOME HEAVY METALS IN MUSCLE OF CYPRINUS CARPIO - Canpolat, Ozgur; Eroglu, Mucahit; Dusukcan, Mustafa (Parlar Scientific Publications (P S P), 2016)
In this study, some heavy metal concentrations (cobalt, cadmium, copper, iron, zinc, chromium, lead and arsenic) were determined in water and in muscle of Cyprinus carpio (Heckel, 1843) to study the potential human risk of consumption and the relationship between the heavy metal load of fish and some of their biological aspects (weight, length and sex). In addition, the transfer factor of heavy metals in C. carpio were determined. It was found that heavy metals accumulated in muscle of C. carpio were higher than that in the surrounding water. The concentration of heavy metals showed differences according to weight, length and sex of fish. The results were discussed and compared with tolerable values for heavy metals provided from the EPA and FAO to determine whether this species has any risk for human consumption.
Keywords: Transfer factor; heavy metal; muscle; accumulation; human consumption; Cyprinus carpio